Human Rights in Islam: Judicial Rights, Sanctions and Penalties - Omar Kasule, Omar Jah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Human Rights in Islam: Judicial Rights, Sanctions and Penalties